PERAN INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DALAM MENGATASI PERDAGANGAN MANUSIA DI INDONESIA TAHUN 2010-2014 - Ghani Wal Arif; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research describes the role of international organization for migration in antisipated human trafficking in Indonesia in 2010-2014. The growth of human trafficking case in Indonesia has incerase a significant, nowdays Indonesia as a state from and to a human trafficking. So the government of Indonesia have to do action to antisipation a case of human trafficking..The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the role of international organization for migration in antisipated human trafficking in Indonesia. The theories applied in this research are pluralism perspective with the international organization concept by Lerroy Bannet.The conclusion of this research about the role of international organization for migration in antisipated human trafficking in Indonesia are international organization for migration has cooperate with the government of Indonesia to create a speciall regulation about human trafficking case, international organization for migration has dealling with Indonesia government to antisipated the human trafficking and cooperation with Indonesian Police to controlling a traffickers.Key words: role, IOM, human and traffick